Changing choices: disabled and chronically ill people's experiences of reconsidering choices. (June 2013) - Baxter, Kate
Objectives: To increase understanding of disabled and chronically ill people's experiences of revisiting choices by considering events that prompted people to reconsider choices; what factors motivated them to act upon these events and what factors affected their experiences of revisiting choices. Methods: A sub-sample of 20 disabled and chronically ill people who took part in a qualitative, longitudinal study exploring choice-making in the context of changing circumstances. Each person was interviewed three times. Analysis focussed on choices that people had been prompted to revisit. Results: Most choices were about health or social care and were revisited within a year due to: changes in health or social circumstances; poorer than expected outcomes; and external interventions. People were motivated to make changes by a desire to maintain independence and control, but perceived short-term costs of decision-making could act as a deterrent. Experiences of revisiting choices were affected by help from other people and emotional strength. Discussion: Making and revisiting choices is complex; people need support to engage with the continual cycle of choice-making. People who instigate revisions of their own accord may be particularly vulnerable to lack of support.